Evaluation of the utility of the Vigileo FloTrac™, LiDCO™, USCOM and CardioQ™ to detect hypovolaemia in conscious volunteers: a proof of concept study1. (February 2015) - O'Loughlin, E.; Ward, M.; Crossley, A.; Hughes, R.; Bremner, A. P.; Corcoran, T.
Summary It is important to detect and treat hypovolaemia; however, detection is particularly challenging in the conscious, spontaneously breathing patient. Eight healthy male volunteers were monitored using four minimally invasive monitors: Vigileo FloTrac™; LiDCOrapid™; USCOM 1A; and CardioQ™ oesophageal Doppler. Monitor output and clinical signs were recorded during incremental venesection of 2.5% estimated blood volume aliquots to a total of 20% blood volume removed. A statistically significant difference from baseline stroke volume was detected after 2.5% blood loss using the LiDCO (p = 0.007), 7.5% blood loss using the USCOM (p = 0.019), and 12.5% blood loss using the CardioQ (p = 0.046) and the FloTrac (p = 0.028). Receiver operator characteristic curves for predicting > 10% blood loss had areas under the curve of 0.68–0.82. The minimally invasive cardiac output devices tested can detect blood loss by a reduction in stroke volume in awake volunteers, and may have a role in guiding fluid replacement in conscious patients with suspected hypovolaemia.